PENGARUH PEMAHAMAN DAN PENGHAYATAN PERAYAAN EKARISTI TERHADAP ORANG MUDA KATOLIK - Veronica Fransilya Oktavia; Ola Rongan Wilhelmus (Lembaga Penelitian STKIP Widya Yuwana, 2021)
The celebration of the Eucharist is the culmination and source of Christian life. The Spirit of the Eucharist in the Parish of St. Pius X Karanganyar is always cultivated in every faithful, especially in the Catholic Youth. Through the Eucharistic Celebration, the faith of Catholic Youth can grow and develop, along with the development of the times. The problem to be investigated is the extent to which the Catholic Youth at St. Pius X Karanganyar understands the meaning and meaning of the Eucharistic Celebration?. The research objective was to analyze the extent to which the understanding and appreciation of the St. Catholic Youth at St. Pius X Karanganyar understood the meaning and meaning of the Eucharistic Celebration. In this study, the authors used quantitative research methods using a questionnaire via google form. Respondents in this study were the Catholic Youth of the St. Petersburg parish. Pius X Karanganyar, who is 15 to 35 years old or not married. From the results of the research analysis showed that the Catholic Youth in the Parish of St. Pius X Karanganyar really understands the understanding and appreciation of Catholic Young People in the Parish of St. Pius X Karanganyar towards the Eucharistic Celebration.